PET Molecular Imaging of Phosphodiesterase 10A: An Early Biomarker of Huntington's Disease Progression. Issue 4 (22nd January 2020) - Fazio, Patrik; Fitzer‐Attas, Cheryl J.; Mrzljak, Ladislav; Bronzova, Juliana; Nag, Sangram; Warner, John H.; Landwehrmeyer, Bernhard; Al‐Tawil, Nabil; Halldin, Christer; Forsberg, Anton; Ware, Jennifer; Dilda, Valentina; et al.
Abstract: Background: Changes in phosphodiesterase 10A enzyme levels may be a suitable biomarker of disease progression in Huntington's disease. Objectives: To evaluate phosphodiesterase 10A PET imaging as a biomarker of HD progression using the radioligand, [ 18 F]MNI‐659. Methods: The cross‐sectional study (NCT02061722) included 45 Huntington's disease gene‐expansion carriers stratified into four disease stages (early and late premanifest and Huntington's disease stages 1 and 2) and 45 age‐ and sex‐matched healthy controls. The primary analysis compared striatal and pallidal phosphodiesterase 10A availability between Huntington's disease gene‐expansion carriers and healthy controls as assessed by [ 18 F]MNI‐659 binding. We assessed changes in phosphodiesterase 10A expression using several PET methodologies and compared with previously proposed measures of Huntington's disease progression (PET imaging of D2/3 receptors and anatomical volume loss on MRI). The longitudinal follow‐up study (NCT02956148) continued evaluation of phosphodiesterase 10A availability in 35 Huntington's disease gene‐expansion carriers at a mean of 18 months from baseline of the cross‐sectional study. Results: Primary analyses revealed that phosphodiesterase 10A availability in caudate, putamen, and globus pallidus was significantly lower in Huntington's disease gene‐expansion carriers versus healthy controls across all stages. Striatal and pallidal phosphodiesterase 10A availability progressively declined in the premanifest stages and appeared to plateau between stages 1 and 2. The percentage decline of phosphodiesterase 10A availability measured cross‐sectionally between Huntington's disease gene‐expansion carriers and healthy controls was greater than that demonstrated by D2/3 receptor availability or volumetric changes. Annualized rates of phosphodiesterase 10A change showed a statistically significant decline between the cross‐sectional study and follow‐up. Conclusions: [ 18 F]MNI‐659 PET imaging is a biologically plausible biomarker of Huntington's disease progression that is more sensitive than the dopamine‐receptor and volumetric methods currently used. © 2020 International Parkinson and Movement Disorder Society